2017
DOI: 10.1038/s41598-017-03364-x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic nutritional index predicts clinical outcome in patients with acute ST-segment elevation myocardial infarction undergoing primary percutaneous coronary intervention

Abstract: We aimed to investigate whether the prognostic nutritional index (PNI), a combined nutritional-inflammatory score based on serum albumin levels and lymphocyte count, was associated with mortality in patients with acute ST-segment elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (pPCI). From September 2011 to November 2014, 309 consecutive patients with STEMI undergoing pPCI were prospectively enrolled. Patients with a combined score of albumin (g/L) + 5 × total lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
87
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(95 citation statements)
references
References 41 publications
5
87
1
2
Order By: Relevance
“…Furthermore, our study is the first to reveal higher mortality among AMI with PEM in the United States. These findings are consistent with the result from the KAMIR‐based study mentioned above and other Asian studies that have used hypoalbuminemia, waist‐to‐hip ratio, body mass index, or other computed measures of nutrition as a surrogate for malnutrition among patients with ST‐elevated AMI undergoing PCI. Our results also concur with studies of PEM in other conditions such as heart failure, acute ischemic stroke, sepsis, hip fractures, and PEM among patients hospitalized in a general medical and surgical floor .…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, our study is the first to reveal higher mortality among AMI with PEM in the United States. These findings are consistent with the result from the KAMIR‐based study mentioned above and other Asian studies that have used hypoalbuminemia, waist‐to‐hip ratio, body mass index, or other computed measures of nutrition as a surrogate for malnutrition among patients with ST‐elevated AMI undergoing PCI. Our results also concur with studies of PEM in other conditions such as heart failure, acute ischemic stroke, sepsis, hip fractures, and PEM among patients hospitalized in a general medical and surgical floor .…”
Section: Discussionsupporting
confidence: 89%
“…PNI was initially reported to be an effective predictor for postoperative complications after surgery (7) and was considered as a predictive nutritional marker for various malignant diseases, such as breast cancer, esophageal cancer, gastric cancer, and so on (8)(9)(10). Besides, some studies have demonstrated that as a nutritional marker, PNI was related to the clinical prognosis of patients with cardiovascular diseases, including coronary atherosclerotic heart disease (CAD) and heart failure (11,12). It is not a rare condition for AIS patients to suffer from malnutrition: the prevalence of undernutrition was around 33% for acute stroke patients at admission (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…These nutritional assessment tools showed prognostic value in patients with malignancy, heart failure, peripheral arterial disease and coronary artery disease [8][9][10][11]. Various studies have shown PNI to be a promising means of risk stratification for stable coronary artery disease (CAD) and acute ST-elevation myocardial infarction (STEMI) patients [11,12]. However, research was lacking in the utility of the CONUT score for the purposes of assessing clinical outcomes in CAD patients.…”
Section: Introductionmentioning
confidence: 99%